0368 Leveraging the Electronic Health Record to Facilitate Shared-Medical Decision Making in a Large Health System: Response to the PAP Recall. (25th May 2022) - Lance, Colleen; Wang, Lu; Foldvary-Schaefer, Nancy; Wyllie, Robert; Baugh, Kristin; Kazaglis, Louis; Carroll, Don; Colwell, Dawn; Hall, Greg; Mehra, Reena
Abstract: Introduction: The positive airway pressure (PAP) device manufacturer recall afflicting ~4 million users has posed a major challenge for the care of patients with sleep disordered breathing. We report on the Cleveland Clinic enterprise-wide response efforts and relevant predictors of medical decision-making surrounding this recall. Methods: A taskforce developed a strategic response to the recall with the goal of distributing enterprise-wide communications; providing key guidance to providers and patients. For patients, a multi-pronged, tiered approach of MyChart messaging, phone and mailings instructing device registration and continuing use of PAP until discussed with the provider was implemented. For providers, an Epic smartphrase, embedded with a tracker, was developed as a resource including details of a decision-making algorithm while awaiting remediation. A team of mid-level providers was trained in the use of the algorithm; and the smartphrase was utilized for targeted virtual visits and communications. Presented is a retrospective cohort analysis of demographics and comorbid predictors between the group of patients advised to continue therapy, versus those advised to discontinue. Wilcoxon rank sum test or t-test was used for comparisons. Results: 15, 759 patients were contacted; message confirmed read/heard for 99.3%. Analysis of smartphrase use yielded 1135 instances (median, IQR): age:61.0 [51, 70];48.5% female, 13.6% African American, body mass index(BMI) 33.5[29, 38.9] kg/m2, apnea hypopnea index(AHI)=22.8[11.7, 46.1] of whom n=770(67.8%) were advised to continued therapy. Predictors of provider guidance to continue versus temporarily hold PAP therapy respectively include: age:63[53, 71] vs. 58[47, 67] p<0.001, female:44% vs. 57%, p<0.001, BMI:33.9[29.5, 39.7] vs. 32.0[28.0, 37.5], p<0.001, AHI:31.9[15.5, 58.0] vs.15.7[9.1, 21.2], p<0.001 and the following comorbidities: hypertension:61.0% vs. 46.3%, p<0.001, coronary artery disease, 11.3% vs. 3.6%, p<0.001, heart failure:2.6% vs. 0.6%, p<0.001, atrial fibrillation:9.5% vs. 2.5%, p<0.001 and chronic obstructive pulmonary disease:5.8% vs. 1.6%, p<0.001, but not diabetes. Conclusion: We conclude that EHR tools can be used to coordinate device recall response efforts and guide both providers and patients. The use of a system smartphrase facilitated provider-patient shared medical decision-making to continue versus temporarily discontinue use of PAP therapy efficiently. Those advised to continue PAP therapy had higher burden of sleep apnea and cardiopulmonary comorbidity. Support (If Any):